Cancer screening among migrants in an Australian cohort; cross-sectional analyses from the 45 and Up Study - O'Connell Dianne; Smith David P; Banks Emily; Weber Marianne F; Sitas Freddy (BMC, 2009)
Abstract Background Limited evidence suggests that people from non-English speaking backgrounds in Australia have lower than average rates of participation in cancer screening programs. The objective of this study was to examine the distribution of bowel, breast and prostate cancer test use by place of birth and years since migration in a large population-based cohort study in Australia. Methods In 2006, screening status, country of birth and other demographic and health related factors were ascertained by self-completed questionnaire among 31,401 (16,126 women and 15,275 men) participants aged 50 or over from the 45 and Up Study in New South Wales. Results 35% of women and 39% of men reported having a bowel cancer test and 57% of men reported having a prostate specific antigen (PSA) test, in the previous 5 years. 72% of women reported having screening mammography in the previous 2 years. Compared to Australian-born women, women from East Asia, Southeast Asia, Continental Western Europe, and North Africa/Middle East had significantly lower rates of bowel testing, with odds ratios (OR; 95%CI) ranging from 0.5 (0.4-0.7) to 0.7 (0.6-0.9); migrants from East Asia (0.5, 0.3-0.7) and North Africa/Middle East (0.5, 0.3-0.9) had significantly lower rates of mammography. Compared to Australian-born men, bowel cancer testing was significantly lower among men from all regions of Asia (OR, 95%CI ranging from 0.4, 0.3-0.6 to 0.6, 0.5-0.9) and Continental Europe (OR, 95%CI ranging from 0.4, 0.3-0.7 to 0.7, 0.6-0.9). Only men from East Asia had significantly lower PSA testing rates than Australian-born men (0.4, 0.3-0.6). As the number of years lived in Australia increased, cancer test use among migrants approached Australian-born rates. Conclusion Certain migrant groups within the population may require targeted intervention to improve their uptake of cancer screening, particularly screening for bowel cancer.